Effect of systematic tuberculosis detection on mortality in young children with severe pneumonia in countries with high incidence of tuberculosis: a stepped-wedge clusterrandomised trial - Marcy, Olivier; Wobudeya, Eric; Font, Hélène; Vessière, Aurélia; Chabala, Chishala; Khosa, Celso; Taguebue, Jean-Voisin; Moh, Raoul; Mwanga-Amumpaire, Juliet; Lounnas, Manon; Mulenga, Veronica; Businge, Gerald; et al. (The Lancet Infectious Diseases, 2022)
Background: Tuberculosis diagnosis might be delayed or missed in children with severe pneumonia because this diagnosis is usually only considered in cases of prolonged symptoms or antibiotic failure. Systematic tuberculosis detection at hospital admission could increase case detection and reduce mortality. Methods: We did a stepped-wedge cluster-randomised trial in 16 hospitals from six countries (Cambodia, Cameroon, Côte d’Ivoire, Mozambique, Uganda, and Zambia) with high incidence of tuberculosis. Children younger than 5 years with WHO-defined severe pneumonia received either the standard of care (control group) or standard of care plus Xpert MTB/RIF Ultra (Xpert Ultra; Cepheid, Sunnyvale, CA, USA) on nasopharyngeal aspirate and stool samples (intervention group). Clusters (hospitals) were progressively switched from control to intervention at 5-week intervals, using a computer-generated random sequence, stratified on incidence rate of tuberculosis at country level, and masked to teams until 5 weeks before switch. We assessed the effect of the intervention on primary (12-week all-cause mortality) and secondary (including tuberculosis diagnosis) outcomes, using generalised linear mixed models. The primary analysis was by intention to treat. We described outcomes in children with severe acute malnutrition in a post hoc analysis. This study is registered with ClinicalTrials.gov (NCT03831906) and the Pan African Clinical Trial Registry (PACTR202101615120643). Findings: From March 21, 2019, to March 30, 2021, we enrolled 1401 children in the control group and 1169 children in the intervention group. In the intervention group, 1140 (97·5%) children had nasopharyngeal aspirates and 942 (80·6%) had their stool collected; 24 (2·1%) had positive Xpert Ultra. At 12 weeks, 110 (7·9%) children in the control group and 91 (7·8%) children in the intervention group had died (adjusted odds ratio [OR] 0·986, 95% CI 0·597–1·630, p=0·957), and 74 (5·3%) children in the control group and 88 (7·5%) children in the intervention group had tuberculosis diagnosed (adjusted OR 1·238, 95% CI 0·696–2·202, p=0·467). In children with severe acute malnutrition, 57 (23·8%) of 240 children in the control group and 53 (17·8%) of 297 children in the intervention group died, and 36 (15·0%) of 240 children in the control group and 56 (18·9%) of 297 children in the intervention group were diagnosed with tuberculosis. The main adverse events associated with nasopharyngeal aspirates were samples with blood in 312 (27·3%) of 1147 children with nasopharyngeal aspirates attempted, dyspnoea or SpO2 less than 95% in 134 (11·4%) of children, and transient respiratory distress or SpO2 less than 90% in 59 (5·2%) children. There was no serious adverse event related to nasopharyngeal aspirates reported during the trial. Interpretation: Systematic molecular tuberculosis detection at hospital admission did not reduce mortality in children with severe pneumonia. High treatment and microbiological confirmation rates support more systematic use of Xpert Ultra in this group, notably in children with severe acute malnutrition.
Keywords: Tuberculosis detection; Young children; Pneumonia; Diagnosis